Cyclic test and analysis of UHTCC‐enhanced buckling‐restrained steel plate shear walls - Tong, Jing‐Zhong; Wang, Ling‐Qi; Wu, Ruo‐Min; Hou, Jian; Li, Qing‐Hua; Xu, Shi‐Lang (Earthquake engineering & structural dynamics, 2024)
The ultra‐high toughness cementitious composite (UHTCC) has the tensile strain‐hardening characteristic and an excellent ability to prevent tensile cracking. To enhance the seismic and durability performance of the conventional buckling‐restrained steel plate shear wall (BRSPSW), UHTCC‐enhanced BRSPSW (UBRSPSW) was proposed in this paper as a new type of lateral bearing system. The buckling of the inner steel plate is restrained by UHTCC‐normal concrete (NC) functionally graded panels, where the panels are composed of UHTCC and NC layers. In this study, experimental and numerical research was carried out on the UBRSPSWs. Six specimens were tested to investigate the seismic behavior of the UBRSPSW. Parameters including the number of stiffeners, the thickness of UHTCC‐NC functionally graded panels, the material of restraining panels, and the gap between the inner steel plate and restraining panels were considered in the test design. Mechanical response and failure modes of the structures under cyclic loads were analyzed. The obtained hysteretic curves and corresponding skeleton curves indicated that the proposed design had excellent seismic performance. Compared to the steel plate shear wall (SPSW), the load‐bearing capacity of UBRSPSW was improved by 13%, respectively. The appearance of macrocracks was delayed by a drift angle of 1.2%. In addition, a refined finite element (FE) model was developed and validated by the results obtained from experiments. The development and distribution of bending moments in the restraining panels were extracted based on the FE method. Then, the loading capacity design method of restraining panels and a theoretical model for controlling the crack width of restraining panels were proposed. The research results of this paper can provide useful suggestions for the seismic design of UBRSPSWs.